Jogos pedagógicos como ferramenta para elucidar as propriedades básicas da molécula de DNA - Paula, Vinícius Sabino de (2022)
The teaching of Genetics is a big challenge Brazilian high school Biology teachers face, since it depends on abstract concepts, illustration of molecular processes and interpretation of flat figures. With the purpose of developing a playful side and energizing the context of molecular genetics, this work has as an objective create and evaluate an educational product, called “Play no DNA”, based in an investigative didactic sequence based in the methods of active learning, as learning based in games and the utilization of digital communication technologies (TDIC). The methodological processes were divided into two complementary sections, with stages of problematization, systematization, contextualization and conclusion, in these phases the students will learn Molecular Genetics, by digital games and investigative teaching. The research was developed in a public school in the town of Nova Mutum/MT, with forty-four enrolled students in the third year of high school. The review of the results showed mixed features (qualitative/quantitative) the utilization of four games of basic level Molecular Genetics were evaluated, the results before and after test identified satisfactory indexes in the students learning, and during the developing of the research, it is noticeable the students position in the process of teaching-learning, the interest and esteem of them in genetics has permitted the scientific literacy and meaningful learning.